Buddhist Ethics of Sexual Intrercourse with AI Robot Citizen - Yodthong, Amnat (Arts of Management Journal, 2021)
This research article has three objectives: 1) to study Buddhist ethics on sexual intercourse with humans; 2) to study Buddhist ethics on sexual intercourse with human corpses, sculptures, and dolls; and 3) to study Buddhist ethics on sexual intercourse with AI robot citizen. This research was documentary research involving content analysis from Pali canon, commentaries, books, and related research. The results showed that the Buddhist ethical norms concerning sexual intercourse with human beings are Five Precepts, especially the Third Precept that involves abstention from sexual misconduct. It has four elements of action: 1) being a forbidden object for oneself, 2) being contented before, during, or after intercourse, 3) every action that lead to the realization of sexual intercourse, and 4) the contact to three organs of the other: anus, urethra, or mouth. For individuals in marriage, cohabitation or intimate relationships, all other individuals outside such partnerships are considered a forbidden object for them. If both parties had sexual intercourse, it is considered sexual misconduct. For the Buddhist ethics, having sex with a human corpse involves three action elements (excluding the first element). If a person in a relationship has sex with a corpse that has three complete organs, it is sexual misconduct. Having sex with statues and dolls that do not look like humans is not sexual misconduct. But people having sex with sex dolls or AI robots that look like humans are considered the same as in the case of human corpses. And the Buddhist ethics of sexual intercourse with an AI robot citizen has the same four action elements as those norms applied to sexual intercourse with a human being, because citizenship entails the equality of status of such a robot with that of a legal human being.